Plan de negocios para la exportación de empanizados de calamar gigante al mercado de Estados Unidos - Baca, Liliana; González, Andreína; Méndez, José; Urrunaga, Tatiana (Journal of Economics, Finance and Administrative Science, 2007)
This article develops a business plan to introduce giant squid in markets in the United States in the form of breaded seafood. The added value that local processing gives to the resource is determinant for obtaining higher prices, as compared to those being paid for squid as raw material, and for entering international markets for fi nished products. The proposed model covers the marketing plan, operations strategies and economic evaluation; the last one shows the economic results expected and the generated profi ts. The article ends by pointing out the critical factors of the business plan: the characteristics of the demand in the destination market and the supply of raw material.